2015
DOI: 10.1007/s11547-015-0548-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose gadobenate dimeglumine-enhanced MRI of the kidney for the differential diagnosis of localized renal lesions

Abstract: ObjectiveTo evaluate low-dose gadobenate dimeglumine-enhanced MRI for the differential diagnosis of malignant renal tumors.MethodsSixty-two consecutive patients with unclear diagnosis at MDCT/ultrasound underwent dynamic CE-MRI of the kidneys with 0.05 mmol/kg gadobenate dimeglumine. Retrospective image evaluation was performed by two blinded readers. Lesion diagnosis at CE-MRI was correlated with findings from histology following tumor resection or from imaging follow-up after at least 1 year. Assessments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This finding supports findings from Khouri Chalouhi et al, who noted significantly superior contrast enhancement with a three‐quarter (0.075 mmol/kg bw) dose of gadobenate compared to a full (0.1 mmol/kg bw) dose of gadoterate. A similar benefit for half‐dose gadobenate has been noted for a range of applications . A clear benefit of using a half dose of gadobenate for combined DSC MRI and conventional T 1 ‐weighted imaging is in patients with severe renal impairment at risk of developing NSF.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This finding supports findings from Khouri Chalouhi et al, who noted significantly superior contrast enhancement with a three‐quarter (0.075 mmol/kg bw) dose of gadobenate compared to a full (0.1 mmol/kg bw) dose of gadoterate. A similar benefit for half‐dose gadobenate has been noted for a range of applications . A clear benefit of using a half dose of gadobenate for combined DSC MRI and conventional T 1 ‐weighted imaging is in patients with severe renal impairment at risk of developing NSF.…”
Section: Discussionmentioning
confidence: 60%
“…A similar benefit for half-dose gadobenate has been noted for a range of applications. [28][29][30][31] A clear benefit of using a half dose of gadobenate for combined DSC MRI and conventional T 1 -weighted imaging is in patients with severe renal impairment at risk of developing NSF. In this regard, safety authority guidelines invariably recommend the use of the lowest effective dose in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…While we identified a single case in which the CT was concerning for AML, the MRI findings were consistent with RCC. MRI has greater tissue sensitivity and previously has been shown to be effective for the differential diagnosis of renal masses that are inconclusive on CT or ultrasound [22]. Therefore, when a renal mass is non-diagnostic on CT, clinicians can consider further workup with to MRI help distinguish between RCC vs AML.…”
Section: Discussionmentioning
confidence: 99%
“…In demonstrating the value of half-dose gadobenate for brain tumor imaging, our study supports the findings of numerous previous studies across a range of MR imaging applications that have confirmed the diagnostic potential of gadobenate at 0.05 mmol/kg body weight. [33][34][35][36] …”
Section: Discussionmentioning
confidence: 99%